Lymphatic malformations: A dilemma in diagnosis and management - Ramashankar; Chandan Prabhakar; Nishit Kumar Shah; Girish Giraddi (Wolters Kluwer Medknow Publications, 2014)
Lymphatic malformations of the head and neck, also known as lymphangiomas or cystic hygromas, are a diverse group of lesions. Lymphangiomas represent benign hamartomatous tumors of lymphatic vessels with a marked predilection for the head, neck and oral cavity. These lesions, like most of the swellings occurring in the neck, frequently pose a dilemma in diagnosis and treatment. This is a case report of a lymphatic malformation which presented as a painless mass in the lower border of mandible.